Development of Circuit Games to Develop Rugged Motoric Ability and Language - Purwatiningsih, Siti Dyah; Bachri, Bachtiar S.; Hasibuan, Rachma (International Journal for Educational and Vocational Studies, 2019)
The purpose of this study is to analyze the feasibility and effectiveness of the circuit game of the recognize me have in developing gross motor skills and children's language in group A at RA Al-Qodir Wage Sidoarjo. This development research use the Dick & Carey research and development model. The result of the development are circuit game products to develop gross motor skill and childrens language in group A. The development of the media includes material about the introduction of indonesian culture, namely traditional clothes in Indonesia. The study was conducted in class A1 at RA Al-Qodir Wage Sidoarjo. Based on the formative test to experts and children obtained qualitative and quantitative data, qualitative data are suggestions from experts and quantitative data in the form of a percentage of child observasion sheets. From the percentage of asessment of formative tests experts and also children, the circuit game is feasible and effective to be used in learning to develop gross motor skills and childrens language in group A in RA Al-Qodir Wage Sidoarjo.